2018
DOI: 10.1063/1.5017537
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the structural phase and octahedral rotation angle in halide perovskites

Abstract: A key to the unique combination of electronic and optical properties in halide perovskite materials lies in their rich structural complexity. However, their radiation sensitive nature limits nanoscale structural characterization requiring dose efficient microscopic techniques in order to determine their structures precisely. In this work, we determine the space-group and directly image the Br halide sites of CsPbBr3, a promising material for optoelectronic applications. Based on the symmetry of high-order Laue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…The XRD pattern shows several diffraction peaks, specifically, peaks at 15.97°, 22.42°, 28.49°, 31.86°, and 39.06°. At room temperature, the CsPb(Br 0.5 Cl 0.5 ) 3 perovskite thin film has an orthorhombic structure in space group Pnma [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. These theoretical data have appeared in consistency to experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…The XRD pattern shows several diffraction peaks, specifically, peaks at 15.97°, 22.42°, 28.49°, 31.86°, and 39.06°. At room temperature, the CsPb(Br 0.5 Cl 0.5 ) 3 perovskite thin film has an orthorhombic structure in space group Pnma [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. These theoretical data have appeared in consistency to experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, this paper also used simulations to determine that defocused-probe iterative ptychography outperformed both focused-probe iterative ptychography and the WDD reconstruction method by approximately a factor of 2 for signal-to-noise. Various authors have applied ptychography to solve materials science questions, including Yang et al (2015 a , 2017), Wang et al (2017), dos Reis et al (2018), Lozano et al (2018), and Fang et al (2019).…”
Section: Phase Contrast Imagingmentioning
confidence: 99%
“…On the other hand, calorimetric investigations on the formation enthalpies of CsPbX perovskites have shown the diminishing order of thermodynamic stability for CsPbCl , CsPbBr , and CsPbI 29 . From various studies it has been reported that CsPbBr undergoes structural phase transitions from orthorhombic to tetragonal and subsequently to cubic at higher temperatures 30 36 .…”
Section: Introductionmentioning
confidence: 99%